NASIONALISME DALAM PERSPEKTIF HUKUM MAQASID AL- SYARIAH - Bachri, Syamsul; Tarmizi, Tarmizi; Habibah, Habibah (Moderation | Journal of Islamic Studies Review, 2021)
This paper discusses "Nationalism in the perspective of Maqasid al-Shari'ah Law" by revealing the problems, namely: (1) How is nationalism in the Qur'an and Hadith, and (2) How is the basis of nationalism (hifdz al-wathan) in the view of maqasid al-syari'ah. Nationalism in the Qur'an is described by Allah Swt in surah Al-Baqarah: 126 about Abraham's love for his country by praying that the country is safe and peaceful and its people are blessed with abundant sustenance. Likewise, nationalism in the Hadith is described about the Prophet Muhammad who loved the land of Mecca and Medina. While the foundations of nationalism (hifdz al-wathan) in the view of maqasid al-syari'ah include: ideological basis, normative basis, psychological basis and sociological basis.